Pranata Kultural Islam Parewa Sara' di Kiru-Kiru Kecamatan Soppengriaja Kabupaten Barru Sulawesi-Selatan - Andi M. Anwar Zaenong (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2009)
Islamic cultural institution in Kiru-kiru, known as Parewa Sara', consist of Imam, Kalte', Bilala', and Doja. It goes hand in hand with Parewa Sara' or Ade', made up of Warenneng as the custom leader, Pabbicara, Parennung, and so on. The term Oadru' or Kall, a title in Parewa Sara', was not known until 1920, when it was established by the leader of Swapraja Soppengriaja, entitled Arung Soppengriaja Parewa Sara' is sample of the cultural basis for the establishment of the Ministry of Religious Affairs in Indonesia Republic It handles the management of mosques, religious preaching, corpse interment. marriage and divorce, almsgiving, inheritance, and the like.